2018
DOI: 10.1186/s12885-018-5159-y
|View full text |Cite
|
Sign up to set email alerts
|

Which nasopharyngeal cancer patients need adaptive radiotherapy?

Abstract: BackgroundAdaptive radiotherapy (ART) has potential benefits in patients with nasopharyngeal cancer (NPC). This retrospective study aimed to identify the factors favoring ART.Materials and methodsForty NPC patients were retrospectively included in this study. All patients received two-phase, volumetric modulated arc radiotherapy (VMAT) and underwent a second computed tomography (CT) for the phase II ART. We generated phantom, non-ART plans by a hybrid method for comparison with ART plans. A paired t-test was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…All three cases received chemotherapy in addition to radiotherapy (2 had cisplatin 100 mg/m 2 and 1 had carboplatin with previous induction chemotherapy). The mean fraction for rescan CT was 21 (range, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. No other primaries were found to be correlated with need for ART ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three cases received chemotherapy in addition to radiotherapy (2 had cisplatin 100 mg/m 2 and 1 had carboplatin with previous induction chemotherapy). The mean fraction for rescan CT was 21 (range, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. No other primaries were found to be correlated with need for ART ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…There is limited data to identify the candidates most likely to benefit from ART (11,26,27). Brown et al stated having more advanced nodal disease, nasopharyngeal primary, being treated with tomotherapy and VMAT compared to IMRT are the factors contributing to re-planning (11).…”
Section: Discussionmentioning
confidence: 99%
“…Most authors advocate for re-planning when these constraints (spinal cord max dose < 45-48 Gy and brainstem max dose < 54 Gy) are breached during radiotherapy. However, studies do not consistently report overdosing of the spinal cord or brainstem with some reporting significant increases in the max dose throughout radiotherapy [8,10,11,19,24,42] and some noting no change [20,40,43,44]. In a prospective cohort study of 22 patients with HNSCC where re-planning was triggered by underdosage of the target volumes (CTV coverage < 95%), overdosage of the parotids (mean dose > 26 Gy), or overdosage of the spinal cord (max dose > 45 Gy) [15], the spinal cord max dose reached the threshold for triggering A-ART in only 3 of 22 patients, whereas parotid gland overdosages occurred in 3 right and 5 left parotids, and CTV undercoverage in 7 instances.…”
Section: Main Textmentioning
confidence: 99%
“…A negative dosimetric change means that it decreased in the dose received (e.g. -10% indicates a 10% decrease in mean parotid dose) "-"information was either not available or was not directly comparable to other volumetric/dosimetric data reported and thus not included " NS " parotid side was not specified "* "parotid side (left or right) was specified; however, ipsilateral and contralateral designation were not specified " Ipsi "ipsilateral parotid [11,24,42] and with several series failing to show a significant overdosage of this structure [20,40,43,44]; clinically significant deviations may only occur in a minority of patients. The effect of adaptive re-planning on the efficacy and tolerability of postoperative radiation for HNSCC is less clear, given the scarcity of data in this cohort.…”
Section: Main Textmentioning
confidence: 99%
“…Tijssen et al [63] published a comprehensive commissioning protocol for the installation of such machines. Adaptive planning for NPC patients has been shown to significantly reduce the dose to the ipsilateral parotid gland [64]. Chuter et al [65] showed that it was feasible for an MR-linear accelerator to utilize current off-line strategies for adaptive planning for head and neck cancers.…”
Section: Magnetic Resonance (Mr)-linear Acceleratormentioning
confidence: 99%